Substitutive trauma: preparing grounds for the Russian attack on Ukraine - Jana Javakhishvili (Torture, 2023)
Unprocessed collective trauma may create fertile soil for political manipulation. This article introduces a new concept, that of "substitutive trauma," which refers to the utilization of unprocessed collective traumatic experiences by political leadership to create shared feelings of victimhood and vengeful attitudes within a population. The analysis explores how a substitutive trauma-based psycho-political dynamic culminated in February 2022 in Russia’s war against Ukraine. The article argues that the community of traumatic stress professionals, studying and understanding macro-societal processes can contribute to reducing and ameliorating such destructive psycho-political developments.